A material for making polymer air fiber and its preparation method and application
By doping antibacterial ceramic powder and magnetic iron tetroxide into polymer air fiber mattress materials, combined with chitosan and jenipine, the existing polymer air fiber mattress preparation process is solved and the mechanical durability is insufficient. The problem of this paper has achieved the improvement of the mechanical properties of the material and the enhancement of versatility, which significantly improves the comfort and hygiene of the mattress.
Patent Information
- Application Number
- CN202411291916.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-14
- Publication Date
- 2025-02-11
- Estimated Expiration
- 2044-09-14
AI Technical Summary
The preparation process of existing polymer air fiber mattresses is complex and the conditions are harsh, which can easily lead to product quality problems, and have high costs, insufficient mechanical durability, and it is easy to collapse after long-term use.
By doping antibacterial TiO2/ZnO/ZrO2 ceramic powder and magnetic iron tetroxide, after tannin modification, it is uniformly dispersed in the TPEE air fiber membrane, combining water-soluble chitosan and genipin, through meltblown and Sol-gel reaction produces polymer air fiber materials with improved mechanical properties and versatility.
The mechanical properties and comprehensive properties of polymer air fiber materials are improved, and the antibacterial, environmental protection, immunity regulation, magnetic therapy and far-infrared heating effects are enhanced, which significantly improves the comfort and hygiene of the mattress.
Smart Images

Figure CN118880605B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of home furnishing technology, and in particular to a material for making high-molecular air fibers, a preparation method and application thereof. Background Art
[0002] The hardness of a mattress affects sleep quality and is an important indicator for evaluating mattress comfort. Both too soft and too hard mattresses can cause discomfort after waking up and even affect the user's health. Polymer air fiber is a new type of mattress material that has many characteristics and advantages. According to the search results, air fiber mattresses are usually made of polymer materials to form a 3D fiber woven structure. Air fiber mattresses are a modern sleep solution that combines comfort, support and easy cleaning to provide users with a healthy and comfortable sleeping environment. The main advantages of this mattress include:
[0003] 1. Good air permeability and strong support: Due to its special structure, the air fiber mattress has good air permeability and provides sufficient support to make sleep more comfortable. The air permeability of this mattress helps keep the mattress dry, reduce the feeling of dampness and stuffiness, and also helps reduce the breeding of mites.
[0004] 2. Washable: Compared with traditional mattresses, air fiber mattresses can be directly washed with water, which makes cleaning the mattress more convenient and can also more effectively remove stains and allergens.
[0005] 3. Adjustable hardness: Some air fiber mattresses are designed with areas of different hardness. Users can adjust the hardness of the mattress according to their preferences and body needs to achieve the best sleeping experience.
[0006] 4. Environmentally friendly materials: Air fiber mattresses are usually made of environmentally friendly materials and do not contain formaldehyde, latex and other substances that may cause allergies. They are a better choice for people with allergies.
[0007] 5. Lightweight and easy to carry: Due to the special nature of the material, air fiber mattresses are usually lighter than traditional mattresses and are easy to carry and place.
[0008] 6. Suitable for specific groups of people: Air fiber mattresses are particularly suitable for teenagers whose bones are developing, people with lumbar discomfort or poor sleep quality, and users who like harder mattresses.
[0009] However, the preparation process of the polymer air fiber is complex and the conditions are harsh, which can easily lead to product quality problems. It also has high costs, insufficient mechanical durability, and is prone to collapse after long-term use. Summary of the invention
[0010] The purpose of the present invention is to propose a material for making polymer air fiber and its preparation method and application. The material has good mechanical properties, and the modified ceramic powder is evenly dispersed in the TPEE air fiber membrane, which has good antibacterial, environmental protection, immunity regulation, magnetic therapy, far-infrared heating and other effects. The prepared material for making polymer air fiber has better comprehensive performance and is a better mattress support material with broad application prospects.
[0011] The technical solution of the present invention is achieved in this way:
[0012] The invention provides a method for preparing a material for making a polymer air fiber. The method comprises the following steps: preparing doped antibacterial TiO2 / ZnO / ZrO2 ceramic powder, depositing magnetic ferroferric oxide, modifying the surface with tannic acid, adding the powder into a water-soluble chitosan solution, immersing a TPEE air fiber membrane prepared by melt-blowing, uniformly dropping a genipin solution, heating for reaction, taking out the membrane, washing it, and drying it to prepare the material for making the polymer air fiber.
[0013] As a further improvement of the present invention, the following steps are included:
[0014] S1. Preparation of doped antibacterial far-infrared ceramic powder: tetrabutyl titanate, zinc acetate, zirconium acetate are added to ethanol, polyvinyl alcohol and thiourea are added, stirred and mixed evenly, hydrochloric acid solution is added dropwise, stirred and reacted, centrifuged, washed, dried, calcined, and ball-milled to obtain doped antibacterial far-infrared ceramic powder;
[0015] S2. Preparation of magnetic doped antibacterial far-infrared ceramic powder: adding the doped antibacterial far-infrared ceramic powder to water, adding ferric chloride and ferrous chloride under inert gas protection, adding ammonia water dropwise, heating and stirring to react, centrifuging, washing, drying, and calcining to obtain magnetic doped antibacterial far-infrared ceramic powder;
[0016] S3. Preparation of modified ceramic powder: adding magnetic doped antibacterial far-infrared ceramic powder to water, adding tannic acid and a catalyst, heating and stirring the reaction, separating with a magnet, washing, and drying to obtain a modified ceramic powder;
[0017] S4. Meltblowing: TPEE is added into the screw injection molding machine, heated and melted for spinning, stretched under the action of hot air, and then pulled by the drafting airflow, blown to the drum, and collected on the drum, and formed into TPEE air fiber film by its own heat bonding;
[0018] S5. Preparation of materials for making polymer air fibers: dissolve water-soluble chitosan in water, add modified ceramic powder, stir and mix evenly, immerse in TPEE air fiber membrane, evenly add genipin solution, heat to react, take out the membrane, wash, and dry to obtain the material for making polymer air fibers.
[0019] As a further improvement of the present invention, the mass ratio of tetrabutyl titanate, zinc acetate, zirconium acetate, polyvinyl alcohol and thiourea in step S1 is 10-13:3-5:2-4:0.5-1:0.2-0.4, the concentration of the hydrochloric acid solution is 1.5-2.5 mol / L, the calcination temperature is 400-600°C, the time is 2-3h, and the ball milling time is 1-2h.
[0020] As a further improvement of the present invention, the mass ratio of the doped antibacterial far-infrared ceramic powder, ferric chloride, ferrous chloride and ammonia water in step S2 is 10-12:3.24:1.26:4-6, the temperature of the heating and stirring reaction is 70-80°C, the time is 3-5h, and the calcination temperature is 400-500°C, and the time is 1-2h.
[0021] As a further improvement of the present invention, the mass ratio of the magnetic doped antibacterial far-infrared ceramic powder, tannic acid and catalyst in step S3 is 10:3-4:0.5-1, the catalyst is a Tris-HCl solution with a pH of 8.5-9.5, the temperature of the heating and stirring reaction is 35-45°C, and the time is 2-4h.
[0022] As a further improvement of the present invention, the melting temperature in step S4 is 205-215°C.
[0023] As a further improvement of the present invention, the water-soluble chitosan in step S5 is carboxymethyl chitosan or chitosan hydrochloride, the mass ratio of the water-soluble chitosan, the modified ceramic powder, and the TPEE air fiber membrane is 7-10:2-3:15-20, the concentration of the genipin solution is 0.1-0.2wt%, the temperature of the heating reaction is 35-45°C, and the time is 1-2h.
[0024] As a further improvement of the present invention, the present invention specifically comprises the following steps:
[0025] S1. Preparation of doped antibacterial far-infrared ceramic powder: 10-13 parts by weight of tetrabutyl titanate, 3-5 parts by weight of zinc acetate, and 2-4 parts by weight of zirconium acetate are added to ethanol, 0.5-1 parts by weight of polyvinyl alcohol and 0.2-0.4 parts by weight of thiourea are added, stirred and mixed evenly, 10-12 parts by weight of 1.5-2.5 mol / L hydrochloric acid solution is added dropwise, stirred and reacted for 3-5 hours, centrifuged, washed, dried, calcined at 400-600°C for 2-3 hours, and ball-milled for 1-2 hours to obtain doped antibacterial far-infrared ceramic powder;
[0026] S2. Preparation of magnetic doped antibacterial far-infrared ceramic powder: 10-12 parts by weight of doped antibacterial far-infrared ceramic powder is added to water, and under the protection of inert gas, 3.24 parts by weight of ferric chloride and 1.26 parts by weight of ferrous chloride are added, and 4-6 parts by weight of ammonia water are added dropwise, heated to 70-80°C, stirred for 3-5h, centrifuged, washed, dried, and calcined at 400-500°C for 1-2h to obtain magnetic doped antibacterial far-infrared ceramic powder;
[0027] S3. Preparation of modified ceramic powder: 10 parts by weight of magnetic doped antibacterial far-infrared ceramic powder was added to water, 3-4 parts by weight of tannic acid and 0.5-1 parts by weight of catalyst were added, heated to 35-45 ° C, stirred for 2-4h, separated by magnet, washed, and dried to obtain modified ceramic powder;
[0028] The catalyst is a Tris-HCl solution with a pH of 8.5-9.5;
[0029] S4. Meltblowing: TPEE is added to the screw injection molding machine, heated to 205-215℃, melted and spun, stretched under the action of hot air, and then pulled by the drafting airflow, blown to the roller, and collected on the roller, relying on its own heat to form a TPEE air fiber film;
[0030] S5. Preparation of materials for making polymer air fibers: dissolve 7-10 parts by weight of water-soluble chitosan in water, add 2-3 parts by weight of modified ceramic powder, stir and mix evenly, immerse 15-20 parts by weight of TPEE air fiber membrane, evenly add 10 parts by weight of 0.1-0.2wt% genipin solution, heat to 35-45°C, react for 1-2h, take out the membrane, wash, and dry to obtain the material for making polymer air fibers.
[0031] The present invention further protects a material for making high molecular weight air fibers obtained by the above-mentioned preparation method.
[0032] The present invention further protects the use of the above-mentioned material for making high molecular weight air fibers in the preparation of mattresses.
[0033] The present invention has the following beneficial effects:
[0034] TPEE air fiber is a 3D mesh fiber structure material. The raw material thermoplastic polyester elastomer is heated and extruded into one piece in water. It has good elasticity and air permeability. It can be directly combined with the fabric layer to form a mattress, and can also be used as a mattress cushioning layer, which helps to obtain good sleep quality.
[0035] The present invention prepares materials for making polymer air fibers, and uses TPEE thermoplastic polyester elastomer (linear block copolymer) as the material to prepare TPEE air fiber membranes through melt-blowing. The fiber membranes have a large specific surface area, and the prepared TPEE air fiber membranes have good mechanical properties, high elasticity, and high rigidity maintenance for long-term use, so that the comfort of the prepared mattress is significantly improved.
[0036] The present invention prepares doped antibacterial TiO2 / ZnO / ZrO2 ceramic powder by sol-gel reaction, and the obtained TiO2 / ZnO / ZrO2 ceramic powder is doped with C, N, and S elements after calcination by adding thiourea. The doping of these non-metallic elements changes the crystal structure of TiO2 and ZnO, and can also inhibit the recombination rate of photogenerated electrons and holes. Compared with pure TiO2 and ZnO, the photocatalytic activity is significantly enhanced, and the defects of photocatalysts TiO2 and ZnO corresponding only in the ultraviolet light region are solved, and its application is greatly broadened, so that the obtained doped antibacterial TiO2 / ZnO / ZrO2 ceramic powder can photocatalytically degrade polluted organic matter such as formaldehyde under the action of visible light, so that the obtained mattress is more environmentally friendly, and at the same time, it also has better antibacterial performance, so that the obtained mattress is more hygienic and safe. At the same time, the obtained TiO2 / ZnO / ZrO2 ceramic powder has a certain far-infrared emission function, can slowly generate heat, so that the user feels a suitable temperature when using the mattress, which is more comfortable.
[0037] Furthermore, magnetic ferroferric oxide is deposited on the surface of TiO2 / ZnO / ZrO2 ceramic powder, which can form a magnetic field, improve sleep state, promote sleep and prolong sleep time, relieve muscle spasms, reduce muscle tension, and also has a certain effect of regulating immunity.
[0038] The surface of the magnetic doped antibacterial far-infrared ceramic powder is modified with tannic acid to make the surface of the particle adhesive and rich in hydroxyl groups, which can be fixed on chitosan through hydrogen bonds with amino groups and carboxyl groups of chitosan. The water-soluble chitosan penetrates into the TPEE air fiber membrane and is cross-linked and adsorbed on the TPEE air fiber membrane under the action of genipin, thereby enhancing the mechanical properties of the TPEE air fiber membrane. The modified ceramic powder is evenly dispersed in the TPEE air fiber membrane, which has good antibacterial, environmental protection, immunity regulation, magnetic therapy, far-infrared heating and other effects, so that the material for making polymer air fibers has better comprehensive performance and is a better mattress support material with broad application prospects. BRIEF DESCRIPTION OF THE DRAWINGS
[0039] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative labor.
[0040] Figure 1 This is a photo of the TPEE air fiber membrane prepared in Example 1 of the present invention. DETAILED DESCRIPTION
[0041] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0042] TPEE TPEE UM551-V.
[0043] Embodiment 1: This embodiment provides a method for preparing a material for making a polymer air fiber, which specifically comprises the following steps:
[0044] S1. Preparation of doped antibacterial far-infrared ceramic powder: 10 g of tetrabutyl titanate, 3 g of zinc acetate, and 2 g of zirconium acetate were added to 500 mL of ethanol, 0.5 g of polyvinyl alcohol and 0.2 g of thiourea were added, and the mixture was stirred for 20 min, 10 g of 1.5 mol / L hydrochloric acid solution was added dropwise, and the mixture was stirred for 3 h, centrifuged, washed, dried, calcined at 400 ° C for 2 h, and ball-milled for 1 h to obtain doped antibacterial far-infrared ceramic powder;
[0045] S2. Preparation of magnetic doped antibacterial far-infrared ceramic powder: 10 g of doped antibacterial far-infrared ceramic powder was added to 500 mL of water, and 3.24 g of ferric chloride and 1.26 g of ferrous chloride were added under nitrogen protection, and 4 g of ammonia water was added dropwise, heated to 70 ° C, stirred for 3 h, centrifuged, washed, dried, and calcined at 400 ° C for 1 h to obtain magnetic doped antibacterial far-infrared ceramic powder;
[0046] S3. Preparation of modified ceramic powder: 10 g of magnetic doped antibacterial far-infrared ceramic powder was added to 500 mL of water, 3 g of tannic acid and 0.5 g of catalyst were added, heated to 35 ° C, stirred for 2 h, separated by magnet, washed, and dried to obtain modified ceramic powder;
[0047] The catalyst is a Tris-HCl solution with a pH of 8.5;
[0048] S4. Meltblowing: TPEE is added to the screw injection molding machine, heated to 205℃, melted and spun, stretched under the action of hot air, and then pulled by the drafting airflow, blown to the roller, and collected on the roller. It relies on its own heat to form a TPEE air fiber film. Figure 1 This is a photo of the prepared TPEE air fiber membrane;
[0049] S5. Preparation of materials for making polymer air fibers: dissolve 7g of carboxymethyl chitosan in 500mL of water, add 2g of modified ceramic powder, stir and mix for 10min, immerse 15g of TPEE air fiber membrane, evenly add 10g of 0.1wt% genipin solution, heat to 35°C, react for 1h, take out the membrane, wash, and dry to obtain the material for making polymer air fibers.
[0050] Embodiment 2: This embodiment provides a method for preparing a material for making a polymer air fiber, which specifically comprises the following steps:
[0051] S1. Preparation of doped antibacterial far-infrared ceramic powder: 13 g of tetrabutyl titanate, 5 g of zinc acetate, and 4 g of zirconium acetate were added to 500 mL of ethanol, 1 g of polyvinyl alcohol and 0.4 g of thiourea were added, and the mixture was stirred for 20 min, 12 g of 2.5 mol / L hydrochloric acid solution was added dropwise, and the mixture was stirred for 5 h, centrifuged, washed, dried, calcined at 600 ° C for 3 h, and ball-milled for 2 h to obtain doped antibacterial far-infrared ceramic powder;
[0052] S2. Preparation of magnetic doped antibacterial far-infrared ceramic powder: 12 g of doped antibacterial far-infrared ceramic powder was added to 500 mL of water, and under nitrogen protection, 3.24 g of ferric chloride and 1.26 g of ferrous chloride were added, and 6 g of ammonia water was added dropwise, heated to 80 ° C, stirred for 5 h, centrifuged, washed, dried, and calcined at 500 ° C for 2 h to obtain magnetic doped antibacterial far-infrared ceramic powder;
[0053] S3. Preparation of modified ceramic powder: 10 g of magnetic doped antibacterial far-infrared ceramic powder was added to 500 mL of water, 4 g of tannic acid and 1 g of catalyst were added, heated to 45 ° C, stirred for 4 h, separated by magnet, washed, and dried to obtain modified ceramic powder;
[0054] The catalyst is a Tris-HCl solution with a pH of 9.5;
[0055] S4. Meltblowing: TPEE is added to the screw injection molding machine, heated to 215℃, melted and spun, stretched under the action of hot air, and then pulled by the drafting airflow, blown to the roller, and collected on the roller, relying on its own heat to form a TPEE air fiber film;
[0056] S5. Preparation of materials for making polymer air fibers: dissolve 10g of carboxymethyl chitosan in 500mL of water, add 3g of modified ceramic powder, stir and mix for 10min, immerse 20g of TPEE air fiber membrane, evenly add 10g of 0.2wt% genipin solution, heat to 45°C, react for 2h, take out the membrane, wash, and dry to obtain the material for making polymer air fibers.
[0057] Embodiment 3: This embodiment provides a method for preparing a material for making a polymer air fiber, which specifically comprises the following steps:
[0058] S1. Preparation of doped antibacterial far-infrared ceramic powder: 11 g of tetrabutyl titanate, 4 g of zinc acetate, and 3 g of zirconium acetate were added to 500 mL of ethanol, 0.7 g of polyvinyl alcohol and 0.3 g of thiourea were added, and the mixture was stirred for 20 min, 11 g of 2 mol / L hydrochloric acid solution was added dropwise, and the mixture was stirred for 4 h, centrifuged, washed, dried, calcined at 500 ° C for 2.5 h, and ball-milled for 1.5 h to obtain doped antibacterial far-infrared ceramic powder;
[0059] S2. Preparation of magnetic doped antibacterial far-infrared ceramic powder: 11 g of doped antibacterial far-infrared ceramic powder was added to 500 mL of water, and 3.24 g of ferric chloride and 1.26 g of ferrous chloride were added under nitrogen protection, and 5 g of ammonia water was added dropwise, heated to 75 ° C, stirred for 4 h, centrifuged, washed, dried, and calcined at 450 ° C for 1.5 h to obtain magnetic doped antibacterial far-infrared ceramic powder;
[0060] S3. Preparation of modified ceramic powder: 10 g of magnetic doped antibacterial far-infrared ceramic powder was added to 500 mL of water, 3.5 g of tannic acid and 0.7 g of catalyst were added, heated to 40 ° C, stirred for 3 h, separated by magnet, washed, and dried to obtain modified ceramic powder;
[0061] The catalyst is a Tris-HCl solution with a pH of 9;
[0062] S4. Meltblowing: TPEE is added to the screw injection molding machine, heated to 210℃, melted and spun, stretched under the action of hot air, and then pulled by the drafting airflow, blown to the roller, and collected on the roller, relying on its own heat to form a TPEE air fiber film;
[0063] S5. Preparation of materials for making polymer air fibers: dissolve 8.5g of carboxymethyl chitosan in 500mL of water, add 2.5g of modified ceramic powder, stir and mix for 10min, immerse 17g of TPEE air fiber membrane, evenly add 10g of 0.15wt% genipin solution, heat to 40°C, react for 1.5h, take out the membrane, wash, and dry to obtain the material for making polymer air fibers.
[0064] Comparative Example 1
[0065] Compared with Example 3, the difference is that thiourea is not added in step S1.
[0066] The details are as follows:
[0067] S1. Preparation of antibacterial far-infrared ceramic powder: Add 11g of tetrabutyl titanate, 4g of zinc acetate, and 3g of zirconium acetate into 500mL of ethanol, add 0.7g of polyvinyl alcohol, stir and mix for 20min, add 11g of 2mol / L hydrochloric acid solution, stir and react for 4h, centrifuge, wash, dry, calcine at 500℃ for 2.5h, and ball mill for 1.5h to obtain antibacterial far-infrared ceramic powder.
[0068] Comparative Example 2
[0069] Compared with Example 3, the difference is that step S2 is not performed.
[0070] The details are as follows:
[0071] S1. Preparation of doped antibacterial far-infrared ceramic powder: 11 g of tetrabutyl titanate, 4 g of zinc acetate, and 3 g of zirconium acetate were added to 500 mL of ethanol, 0.7 g of polyvinyl alcohol and 0.3 g of thiourea were added, and the mixture was stirred for 20 min, 11 g of 2 mol / L hydrochloric acid solution was added dropwise, and the mixture was stirred for 4 h, centrifuged, washed, dried, calcined at 500 ° C for 2.5 h, and ball-milled for 1.5 h to obtain doped antibacterial far-infrared ceramic powder;
[0072] S2. Preparation of modified ceramic powder: 10 g of doped antibacterial far-infrared ceramic powder was added to 500 mL of water, 3.5 g of tannic acid and 0.7 g of catalyst were added, heated to 40° C., stirred for reaction for 3 h, centrifuged, washed, and dried to obtain modified ceramic powder;
[0073] The catalyst is a Tris-HCl solution with a pH of 9;
[0074] S3. Meltblowing: TPEE is added to the screw injection molding machine, heated to 210℃, melted and spun, stretched under the action of hot air, and then pulled by the drafting airflow, blown to the roller, and collected on the roller, relying on its own heat to form a TPEE air fiber film;
[0075] S4. Preparation of materials for making polymer air fibers: dissolve 8.5g of carboxymethyl chitosan in 500mL of water, add 2.5g of modified ceramic powder, stir and mix for 10min, immerse 17g of TPEE air fiber membrane, evenly add 10g of 0.15wt% genipin solution, heat to 40°C, react for 1.5h, take out the membrane, wash, and dry to obtain the material for making polymer air fibers.
[0076] Comparative Example 3
[0077] Compared with Example 3, the difference is that step S3 is not performed.
[0078] The details are as follows:
[0079] S1. Preparation of doped antibacterial far-infrared ceramic powder: 11 g of tetrabutyl titanate, 4 g of zinc acetate, and 3 g of zirconium acetate were added to 500 mL of ethanol, 0.7 g of polyvinyl alcohol and 0.3 g of thiourea were added, and the mixture was stirred for 20 min, 11 g of 2 mol / L hydrochloric acid solution was added dropwise, and the mixture was stirred for 4 h, centrifuged, washed, dried, calcined at 500 ° C for 2.5 h, and ball-milled for 1.5 h to obtain doped antibacterial far-infrared ceramic powder;
[0080] S2. Preparation of magnetic doped antibacterial far-infrared ceramic powder: 11 g of doped antibacterial far-infrared ceramic powder was added to 500 mL of water, and 3.24 g of ferric chloride and 1.26 g of ferrous chloride were added under nitrogen protection, and 5 g of ammonia water was added dropwise, heated to 75 ° C, stirred for 4 h, centrifuged, washed, dried, and calcined at 450 ° C for 1.5 h to obtain magnetic doped antibacterial far-infrared ceramic powder;
[0081] S3. Meltblowing: TPEE is added to the screw injection molding machine, heated to 210℃, melted and spun, stretched under the action of hot air, and then pulled by the drafting airflow, blown to the roller, and collected on the roller, relying on its own heat to form a TPEE air fiber film;
[0082] S4. Preparation of materials for making polymer air fibers: dissolve 8.5g of carboxymethyl chitosan in 500mL of water, add 2.5g of magnetic-doped antibacterial far-infrared ceramic powder, stir and mix for 10min, immerse 17g of TPEE air fiber membrane, evenly add 10g of 0.15wt% genipin solution, heat to 40°C, react for 1.5h, take out the membrane, wash, and dry to obtain the material for making polymer air fibers.
[0083] Comparative Example 4
[0084] Compared with Example 3, the difference is that no modified ceramic powder is added in step S5.
[0085] The details are as follows:
[0086] S5. Preparation of materials for making polymer air fibers: Dissolve 8.5g of carboxymethyl chitosan in 500mL of water, stir and mix for 10min, immerse 17g of TPEE air fiber membrane, evenly add 10g of 0.15wt% genipin solution, heat to 40°C, react for 1.5h, take out the membrane, wash, and dry to obtain the material for making polymer air fibers.
[0087] Comparative Example 5
[0088] Compared with Example 3, the difference is that carboxymethyl chitosan is not added in step S5.
[0089] The details are as follows:
[0090] S5. Preparation of materials for making polymer air fibers: Add 2.5 g of modified ceramic powder into 500 mL of water, stir and mix for 10 min, immerse in 17 g of TPEE air fiber membrane, heat to 40°C, react for 1.5 h, take out the membrane, wash, and dry to obtain the material for making polymer air fibers.
[0091] Test Example 1
[0092] The materials for making high molecular weight air fibers obtained in Examples 1-3 and Comparative Examples 1-5 were tested using an oscillation method (GB / T20944.3-2008).
[0093] Test bacteria: Escherichia coli ATCC25922, Staphylococcus aureus ATCC6538.
[0094] The results are shown in Table 1.
[0095] Table 1
[0096]
[0097]
[0098] It can be seen from the above table that the materials for making the polymer air fibers prepared in Examples 1-3 of the present invention have good antibacterial properties.
[0099] Test Example 2
[0100] The materials for making high molecular weight air fibers prepared in Examples 1-3 and Comparative Examples 1-5 of the present invention are used as the support layer of a mattress with a thickness of 6 cm and a density of 55 kg / m 3 , sponge as cushioning layer, thickness 4cm, density 20kg / cm 3 , mattresses were prepared using cotton cloth as the surface layer and tested.
[0101] Thermal comfort test The test instrument uses the American iButton temperature recorder, and the specific parameters are as follows: temperature measurement range -35 to 70℃, sampling speed 1 time / min, sampling resolution 0.5℃, accuracy ±0.5℃. Before the test, the mattress needs to be placed in an environment with a room temperature of (23±0.5)℃ and a relative humidity of (50±5)% for 24 hours. The test points are selected from the four parts of the human body that are in contact with the mattress when lying on the back, namely the back. At the test point, the temperature recorder is attached to the surface of the bed sheet with a thin breathable tape, and the experiment begins after the indoor environment meets the experimental conditions. Each experiment lasts 30 minutes. After the data collection is completed, it is analyzed. The overall interface temperature is calculated from the local interface temperature. During the experiment, the subjects were tested for subjective temperature perception and subjective thermal comfort evaluation, and the average value was taken. The subjective temperature perception evaluation scale is shown in Table 2, and the subjective comfort evaluation scale is shown in Table 3.
[0102] Table 2
[0103]
[0104] Table 3
[0105]
[0106]
[0107] The back temperature change results are shown in Table 4.
[0108] Table 4 Back temperature change table
[0109]
[0110] It can be seen from the above table that the temperature of the mattresses prepared by the materials for making the high molecular weight air fibers prepared in Examples 1-3 of the present invention is higher and more suitable.
[0111] The scoring results are shown in Table 4.
[0112] Table 5
[0113] Group Subjective temperature rating Subjective thermal comfort rating Example 1 0.25 -2.10 Example 2 0.27 -2.07 Example 3 0.22 -2.15 Comparative Example 1 0.10 -1.74 Comparative Example 2 0.12 -1.89 Comparative Example 3 -0.14 -0.52 Comparative Example 4 -1.54 1.58 Comparative Example 5 -1.07 1.17
[0114] It can be seen from the above table that the subjective temperature of the mattresses prepared by the materials for making the high molecular weight air fibers prepared in Examples 1-3 of the present invention is moderate and more comfortable.
[0115] Test Example 3
[0116] The materials for making high molecular weight air fibers prepared in Examples 1-3 and Comparative Examples 1-5 of the present invention are used as the support layer of a mattress with a thickness of 6 cm and a density of 55 kg / m 3 , sponge as cushioning layer, thickness 4cm, density 20kg / cm 3, mattresses were prepared using cotton cloth as the surface layer and tested.
[0117] This test uses the MCK-ZI intelligent display controller to measure the force-displacement curve of the mattress sample. The test was carried out in an environment with room temperature (23±2)℃ and relative humidity (50±5)%. Before the test, the pressure plate was raised, the mattress sample was placed on the experimental table, and the position of the pressure plate was adjusted so that it was just in the middle of the mattress sample. During the test, the amount of subsidence of the mattress sample at a force of 110N was measured. The test was performed 3 times, and the average value was taken to calculate the comprehensive stiffness K value of the mattress sample. The K value is proportional to the hardness of the mattress. The larger the comprehensive stiffness K value, the harder the mattress, and the smaller the comprehensive stiffness K value, the softer the mattress.
[0118] The results are shown in Table 6.
[0119] Table 6
[0120] Group Comprehensive stiffness K value Example 1 4.56 Example 2 4.55 Example 3 4.59 Comparative Example 1 4.53 Comparative Example 2 4.51 Comparative Example 3 4.45 Comparative Example 4 4.07 Comparative Example 5 4.20
[0121] It can be seen from the above table that the mattresses prepared from the materials for making the high molecular weight air fibers obtained in Examples 1-3 of the present invention have better comprehensive stiffness K values.
[0122] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for preparing a material for making a polymer air fiber, characterized in that: The following steps are involved: S1. Preparation of doped antibacterial far-infrared ceramic powder: tetrabutyl titanate, zinc acetate, zirconium acetate are added to ethanol, polyvinyl alcohol and thiourea are added, stirred and mixed evenly, hydrochloric acid solution is added dropwise, stirred and reacted, centrifuged, washed, dried, calcined, and ball-milled to obtain doped antibacterial far-infrared ceramic powder; S2. Preparation of magnetic doped antibacterial far-infrared ceramic powder: adding the doped antibacterial far-infrared ceramic powder to water, adding ferric chloride and ferrous chloride under inert gas protection, adding ammonia water dropwise, heating and stirring to react, centrifuging, washing, drying, and calcining to obtain magnetic doped antibacterial far-infrared ceramic powder; S3. Preparation of modified ceramic powder: adding magnetic doped antibacterial far-infrared ceramic powder to water, adding tannic acid and a catalyst, heating and stirring the reaction, separating with a magnet, washing, and drying to obtain a modified ceramic powder; S4. Meltblowing: TPEE is added into the screw injection molding machine, heated and melted for spinning, stretched under the action of hot air, and then pulled by the drafting airflow, blown to the drum, and collected on the drum, and formed into TPEE air fiber film by its own heat bonding; S5. Preparation of materials for making polymer air fibers: dissolve water-soluble chitosan in water, add modified ceramic powder, stir and mix evenly, immerse in TPEE air fiber membrane, evenly add genipin solution, heat to react, take out the membrane, wash, and dry to obtain the material for making polymer air fibers.
2. The preparation method according to claim 1, characterized in that: In step S1, the mass ratio of tetrabutyl titanate, zinc acetate, zirconium acetate, polyvinyl alcohol and thiourea is 10-13:3-5:2-4:0.5-1:0.2-0.4, the concentration of the hydrochloric acid solution is 1.5-2.5 mol / L, the calcination temperature is 400-600°C, the time is 2-3h, and the ball milling time is 1-2h.
3. The preparation method according to claim 1, characterized in that: The mass ratio of the doped antibacterial far-infrared ceramic powder, ferric chloride, ferrous chloride and ammonia water in step S2 is 10-12: 3.24:1.26:4-6, the temperature of the heating and stirring reaction is 70-80°C, the time is 3-5h, the temperature of the calcination is 400-500°C, the time is 1-2h.
4. The preparation method according to claim 1, characterized in that: The mass ratio of the magnetic doped antibacterial far-infrared ceramic powder, tannic acid and catalyst in step S3 is 10:3-4:0.5-1, the catalyst is a Tris-HCl solution with a pH of 8.5-9.5, the temperature of the heating and stirring reaction is 35-45°C, and the time is 2-4h.
5. The preparation method according to claim 1, characterized in that: The melting temperature in step S4 is 205-215°C.
6. The preparation method according to claim 1, characterized in that: The water-soluble chitosan in step S5 is carboxymethyl chitosan or chitosan hydrochloride, the mass ratio of the water-soluble chitosan, modified ceramic powder, and TPEE air fiber membrane is 7-10:2-3:15-20, the concentration of the genipin solution is 0.1-0.2wt%, the temperature of the heating reaction is 35-45°C, and the time is 1-2h.
7. The preparation method according to claim 1, characterized in that: The specific steps include: S1. Preparation of doped antibacterial far-infrared ceramic powder: 10-13 parts by weight of tetrabutyl titanate, 3-5 parts by weight of zinc acetate, and 2-4 parts by weight of zirconium acetate are added to ethanol, 0.5-1 parts by weight of polyvinyl alcohol and 0.2-0.4 parts by weight of thiourea are added, stirred and mixed evenly, 10-12 parts by weight of 1.5-2.5 mol / L hydrochloric acid solution is added dropwise, stirred and reacted for 3-5 hours, centrifuged, washed, dried, calcined at 400-600°C for 2-3 hours, and ball-milled for 1-2 hours to obtain doped antibacterial far-infrared ceramic powder; S2. Preparation of magnetic doped antibacterial far-infrared ceramic powder: 10-12 parts by weight of doped antibacterial far-infrared ceramic powder is added to water, and under the protection of inert gas, 3.24 parts by weight of ferric chloride and 1.26 parts by weight of ferrous chloride are added, and 4-6 parts by weight of ammonia water are added dropwise, heated to 70-80°C, stirred for 3-5h, centrifuged, washed, dried, and calcined at 400-500°C for 1-2h to obtain magnetic doped antibacterial far-infrared ceramic powder; S3. Preparation of modified ceramic powder: 10 parts by weight of magnetic doped antibacterial far-infrared ceramic powder was added to water, 3-4 parts by weight of tannic acid and 0.5-1 parts by weight of catalyst were added, heated to 35-45 ° C, stirred for 2-4h, separated by magnet, washed, and dried to obtain modified ceramic powder; The catalyst is a Tris-HCl solution with a pH of 8.5-9.5; S4. Meltblowing: TPEE is added to the screw injection molding machine, heated to 205-215℃, melted and spun, stretched under the action of hot air, and then pulled by the drafting airflow, blown to the roller, and collected on the roller, relying on its own heat to form a TPEE air fiber film; S5. Preparation of materials for making polymer air fibers: dissolve 7-10 parts by weight of water-soluble chitosan in water, add 2-3 parts by weight of modified ceramic powder, stir and mix evenly, immerse 15-20 parts by weight of TPEE air fiber membrane, evenly add 10 parts by weight of 0.1-0.2wt% genipin solution, heat to 35-45°C, react for 1-2h, take out the membrane, wash, and dry to obtain the material for making polymer air fibers.
8. A material for making high molecular weight air fibers obtained by the preparation method according to any one of claims 1 to 7.
9. Use of the material for making high molecular weight air fibers as claimed in claim 8 in preparing mattresses.
Citation Information
Patent Citations
Complex fiber with functions of magnetism, far infrared and anti-bacteria
CN108842217A
Fiber towel and preparation method thereof
CN118127817A